Bio-inspired neural networks for decision-making mechanisms and neuromodulation for motor control in a differential robot - Guerrero-Criollo, Roberto Jose; Castaño-López, Jason Alejandro; Hurtado-López, Julián; Ramirez-Moreno, David Fernando (Frontiers in Neurorobotics, 2023)
The purpose of this work is to modulate the motor control of an automaton in exploration behaviors. In order to achieve this purpose, we propose a bio-inspired neural network with neuromodulation for motor control. In this work, we have adapted and applied cortical synaptic circuits, such as short-term memory circuits, competitive neural networks class winner-take-all (WTA), modulation neural networks and non-linear oscillation circuits, to make the automaton capable to avoid obstacles and exploring simulated and real environments. The performance achieved by using a biologically inspired neural network to solve the task in question is similar to several works mentioned in the specialized literature. Additionally, this work contributed to the bridge between computational neuroscience and robotics fields.